Solving Fuzzy Nonlinear Equations Via Stirling’s-Like Method - Umar Omesa, Audu; Mamat, Mustafa; Mohammed Sulaiman, Ibrahim; Yusuf Waziri, Muhammad; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
This paper presents a Stirling-like method (SM) for solving fuzzy nonlinear equation, where the SM steps are computed at every iteration. In this method, we combine successive substitutionâ€™s and Newtonâ€™s method. Numerical experiments with encouraging results are presented that shows the efficiency of the proposed method. Â Â Â